The influence of basic plan parameters on calculated small field output factors – A multicenter study. (August 2021) - Falco, Maria Daniela; Fusella, Marco; Clemente, Stefania; Fiandra, Christian; Gallio, Elena; Garibaldi, Cristina; Bagalà, Paolo; Borzì, Giuseppina; Casale, Michelina; Casati, Marta; Consorti, Rita; Delana, Anna; et al.
Highlights: Algorithm and Field or grid size are predictive of OF calculation accuracy in TPS. Modern TPSs slightly overestimate the calculated small fields OFs. For Monte Carlo and AAA algorithms, a grid resolution of 1 mm is recommended. Abstract: Purpose: The influence of basic plan parameters such as slice thickness, grid resolution, algorithm type and field size on calculated small field output factors (OFs) was evaluated in a multicentric study. Methods and materials: Three computational homogeneous water phantoms with slice thicknesses (ST) 1, 2 and 3 mm were shared among twenty-one centers to calculate OFs for 1x1, 2x2 and 3x3 cm 2 field sizes (FSs) (normalized to 10x10 cm 2 FS), with their own treatment planning system (TPS) and the energy clinically used for stereotactic body radiation therapy delivery. OFs were calculated for each combination of grid resolution (GR) (1, 2 and 3 mm) and ST and finally compared with the OFs measured for the TPS commissioning. A multivariate analysis was performed to test the effect of basic plan parameters on calculated OFs. Results: A total of 509 data points were collected. Calculated OFs are slightly higher than measured ones. The multivariate analysis showed that Center, GR, algorithm type, and FS are predictive variables of the difference between calculated and measured OFs (p < 0.001). As FS decreases, the spread in the difference between calculated and measured OFs became larger when increasing the GR. Monte Carlo and Analytical Anisotropic Algorithms, presented a dependence on GR (p < 0.01), while Collapsed Cone Convolution and Acuros did not. The effect of the ST was found to be negligible. Conclusions: Modern TPSs slightly overestimate the calculated small field OFs compared with measured ones. Grid resolution, algorithm, center number and field size influence the calculation of small field OFs.